Evaluation of the key words used in articles of the Acta Cirurgica Brasileira from 1997 to 2012 - Teixeira,Renan Kleber Costa (2012)
PURPOSE: To evaluate the key words used in Acta Cirurgica Brasileira from 1997 to 2012. METHODS: All the key words of all articles published in regular issues between 1997 and 2012 were analyzed, ensuring that these key words were in the MeSH database (Medical Subjects Headings) and the most used subject headings and most wrong repeated key words were ranked. RESULTS: > 4230 key words used in 990 articles were analyzed. Only 579 key words (13.68%) were not in the MeSH database, considering that there was a statistically significant decrease over the years (p<0.001). The three most used key words were Rats, Dogs and Wound healing. Among the wrong ones, the key words were Adhesions, Experimental surgery and Anatomosis. CONCLUSION: There was a gradual improvement in the amount of key words used that belonged to the MeSH database, and there were 618 articles (62.42%) with all key words correct.